MANAGEMENT OF RURAL – URBAN MIGRATION AND ECONOMIC DEVELOPMENT IN NIGERIA: THE CASE OF ANAMBRA STATE (2004 – 2010) - Emma E.O. Chukwuemeka; Okoye –Nebo Chidiebere; Elizabeth Okechukwu (European Scientific Journal, ESJ, 2013)
This study examined Management of Rural-Urban Migration and Economic Development in Nigeria: The case of Anambra State. Relevant data were elicited from both the primary and secondary sources. Questionnaire was the main instrument for data collection. Three hundred and ninety- nine (399) copies of questionnaire were administered to the respondents of the three local government areas studied. Subsequently, data were analyzed with simple percentage, and presented in frequency tables for easy comprehension. The hypotheses were also tested using chi-square parametric test (x'2). The study revealed among other things that: The housing estate are mostly owned by individuals or private companies and are very expensive; the transformers provided are not commensurate with the population increase; the state lacks available lands for agriculture as most of the lands are affected by erosion, floods and landslides. The researchers recommended among others that: Government should be in partnership with the people and companies to reduce accommodation problems, government should ensure that materials used for transformers are adequate while making sure that the agricultural extension programmes are well financed in real terms as this will help manage the problems of rural-urban migration and bring about development.